Psychosocial functioning in integrated treatment of co-occurring posttraumatic stress disorder and alcohol use disorder. (October 2021) - Lyons, Robert; Panza, Kaitlyn E.; Helm, Jonathan; Angkaw, Abigail C.; Straus, Elizabeth; Norman, Sonya B.
Abstract: Co-occurring posttraumatic stress disorder and alcohol use disorder (PTSD/AUD) is associated with poorer psychosocial functioning than either disorder alone; however, it is unclear if psychosocial functioning improves in treatment for PTSD/AUD. This study examined if psychosocial functioning improved in integrated treatments for PTSD/AUD, and if changes in PTSD severity and percentage heavy drinking days (PHDD) during treatment were associated with functioning outcomes. 119 veterans with PTSD/AUD randomized to receive either Concurrent Treatment of PTSD and Substance Use Disorders using Prolonged Exposure or Seeking Safety completed measures of functioning (Medical Outcomes Survey SF-36), PTSD (Clinician Administered PTSD Scale for DSM-5), and alcohol use (Timeline Follow-Back) at baseline, posttreatment, 3- and 6-month follow-ups. Our findings suggest that psychosocial functioning improved to a statistically significant degree with no significant differences between conditions. Reductions in PTSD severity during treatment were associated with psychosocial functioning improvements, whereas reductions in PHDD were associated with improvement in role impairment at posttreatment. Although psychosocial functioning improves to a statistically significant degree in interventions designed to treat PTSD/AUD, these improvements do not represent clinically meaningful improvements in patients' abilities to navigate important roles. Findings underscore the need to study how to best treat psychosocial functioning impairment in PTSD/AUD. Highlights: Integrated treatment for PTSD/AUD may not improve psychosocial functioning. Reductions in PTSD severity are associated with improved psychosocial functioning. Reductions in drinking are not associated with improved psychosocial functioning.